Diagnóstico laboratorial de flebovírus (Vírus Toscana). - Fátima Amaro; M Grazia Ciufolini; Giulietta Venturi; Cristiano Fiorentini; Maria João Alves (Acta Médica Portuguesa, 2007)
Viruses from the Phlebovirus genus (family Bunyaviridae) are arboviruses that can be transmitted to humans by mosquitoes (Rift Valey virus) or by sandflies. In phleboviruses group we can find the etiological agents for Sandfly Fever (SF) that is spread in the Mediterranean basin, Middle East, Pakistan and India. In Portugal, the importance of phleboviruses to the Public Health is recognized because there have been detected cases of Toscana virus infection wich is responsible for severe cases of SF that involve encephalitis/meningitis. On the other hand, Phlebotomus perniciosus, one of Toscana virus vectors, is widespread in Portugal.